Analysis of ultra-fast mode-locked fiber laser - Suherman, Alexander. (2012)
Passively mode-locked fiber lasers are among the best optical pulsed sources available today due to their simplicity and their ability to generate transform-limited optical pulses in the picosecond and subpicosecond regimes.